Consumo, calidad nutricional y digestibilidad aparente de morera (Morus alba) y pasto estrella (Cynodon nlemfuensis) en cabras - Rodríguez-Zamora, Jessie (2013)
Intake, nutritional quality, and apparent digestibility of mulberry (Morus alba) and star grass (Cynodon nlemfuensis) in goats. The quality, selection, intake, and apparent digestibility of mulberry and star grass in goats, offered fresh or partially dehydrated, were evaluated. The experiment was carried out at the “Alfredo Volio Mata” Experiment Station of the University of Costa Rica. Harvested forage was fed to 12 Saanen, Toggenburg and Lamancha non-lactating and non-pregnant goats, distributed in a randomized 2x2 factorial design, with an average live weight of 37±5 kg. The treatments were a) fresh star grass, b) partially dehydrated star grass, c) fresh mulberry, and d) partially dehydrated mulberry. Forage was offered chopped to the animals. Dry matter intake was 0.93, 0.76, 1.17 and 1.12 kg.animal-1.day-1 (±0.09) for fresh star grass, partially dehydrated star grass, fresh mulberry, and partially dehydrated mulberry, respectively. This represented 2.62, 2.09, 3.17 and 3.13% (±0.24) of body weight. Crude protein intake was lower with partially dehydrated star grass and higher with fresh mulberry (75.2 vs. 135.4 g.animal-1.day-1). Apparent digestibility was not statistically different between treatments; it was on average 49.18% for DM, 59.82% for CP, 57.83% for NDF, and 55.30% for ADF. This study demonstrates that the forage species significantly affects voluntary dry matter intake in goats; however, dry matter content of the forages used in this study did not affect DM intake.